Processed Fruit Marketing Alternatives for Florida Citrus Growers - Robert A. Morris (EDIS)
FE831, a 12-page fact sheet by Robert A. Morris, discusses several options available for pricing citrus fruit, tradeoffs between risk and gain for each, and potential issues for the future of citrus pricing. Published by the UF Department of Food and Resource Economics, April 2010.